FACTORS OF HUMAN BEHAVIOR FORMATION IN SOCIETY (International journal of artificial intelligence, 2026)
This topic focuses on the theoretical and practical aspects of analyzing human behavior in social work and sociology. It examines the interaction between individuals and the social environment, as well as the influence of social roles, values, and norms on behavior. The study also highlights the role of human factors in addressing social issues and the importance of behavioral models. It contributes to developing effective approaches in social work practice.